Leakage current conduction mechanism of three-dimensional capacitors embedded in through-silicon vias - Lin, Ye (2020)
Leakage current conduction mechanism of three-dimensional capacitors embedded in through-silicon vias has been investigated for two sets of test vehicles, namely "sputtering samples" and "atomic layer deposition (ALD) samples". Schottky emission, hopping conduction, Poole-Frenkel emission, and Fowler-Nordheim tunneling have been identified for these samples, respectively. Self-consistent parameters are extracted through the analysis of leakage current conduction mechanisms: (1) optical dielectric constant (1.98-3.69), and (2) Schottky barrier height (1.66-2.21 eV). In terms of leakage current density, the ALD process is preferred over the sputtering process during the fabrication because the sputtered electrodes result in more traps in the vertical dielectric layers.